Evaluation of silvestrol as a potential therapeutic agent for pediatric COVID-19: an interpreted computational and phytochemistry approach - Zhang, Yi; Pu, Shanshan; Wang, Hui (Frontiers in Pharmacology, 2025)
BackgroundThe persistent COVID-19 disease, induced by SARS-CoV-2, sparked great questions about the safety and efficacy of the existing therapies in pediatric patients. The currently available antiviral drugs for treating COVID-19, either remdesivir or monoclonal antibodies, are primarily designed for adults. In many cases, their development has been hindered by concerns about safety and pediatric populations.ObjectivesIn the present study, we consider Silvestrol, a natural product derived from Euphorbia hirta, as a potential treatment for pediatric COVID-19.MethodsThe molecular docking studies revealed that Silvestrol exhibits a highly competitive binding affinity of −7.5 kcal/mol with the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein, indicating that it may inhibit viral entry. In order to learn more about the dynamics of this interaction, the molecular dynamics (MD) simulations were carried out, which proved that the protein was stabilized in 150 ns, whereas the ligand showed conformational changes to be fit in the binding pocket, and finally stabilizing. The characterization of the pharmacophore also revealed important interaction points, including four hydrogen bond donors, 12 hydrogen bond acceptors, and eight hydrophobic sites, which increase its binding potential.ResultsThe favorable ADMET analysis predicted the pharmacokinetic properties of Silvestrol, which exhibited tumor-killing characteristics in vitro and in vivo activities, and an LD50 of 2,300 mg/kg (toxicity 5), implying a high safety margin. Most toxicity endpoints of Silvestrol were likely to be inactive; however, there was a chance of immunotoxicity and nutritional toxicity, which require further investigation. Its reactivity in antiviral interactions has been confirmed by its reasonable value of 0.20606 eV obtained through the DFT analysis.ConclusionThe observations suggest that Silvestrol is a promising agent for treating COVID-19 in children, as it exhibits a potent antiviral effect, low toxicity, and favorable pharmacokinetics. Further preclinical and clinical testing is needed to demonstrate its effectiveness and safety in children.